Impact of freshwater inputs on the spatial structure of benthic macroinvertebrate communities in two landlocked coastal lagoons - Félix, PM (2016)
Landlocked lagoons are naturally stressed environments. They are strongly influenced by freshwater input which not only varies naturally, but which is also impacted by anthropogenic activities. This study investigated the direct influence of freshwater discharges on the distribution patterns and abundance of benthic communities in two neighbouring landlocked coastal lagoons, assessing the whole system and the confluence area of each tributary. Sampling occurred in the wet and dry seasons of 2011 at two distances from freshwater discharge locations. Both lagoons were colonized by species from tw o different pools, freshwater and marine. Freshwater flow rates had a direct influence on the spatial structure of the benthic communities of brackish-water/freshwater interface areas, where also specific taxa can act as early indicators of freshwater input variations. The intensity of this influence is highly dependent on lagoon size, creating spatial heterogeneity or affecting the entire system. The benthic fauna at the confluence of the tributary that depends almost exclusively on groundwater showed the lowest variability, suggesting that the biogeochemical nature of the groundwater may be a central cause for setting specific ecotones. The results suggest that benthic communities of landlocked coastal lagoons can be highly impacted by flow reduction from freshwater aquifers under drought conditions or water abstraction activities.